THE RIDER OF THE SKY (VASYL’ BARKA – A PAINTER) - Parovatkina, H. Y. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
For the first time the article reveals a so far recondite facet of Vasyl’ Barka’s creative endowment – the art of painting. On examining his artistic paintings, exhibited in the National Museum of Literature of Ukraine a few years ago, the author of the article briefly acquaints with the exhibits of the display, draws parallels with the visual art works by Čiurlionis and Roerich.